2016
DOI: 10.1021/jacs.6b11332
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) Activation of Nitrite: Nitrosation of Nucleophiles and Generation of NO by Thiols

Abstract: Nitrite (NO) and nitroso compounds (E-NO, E = RS, RO, and RN) in mammalian plasma and cells serve important roles in nitric oxide (NO) dependent as well as NO independent signaling. Employing an electron deficient β-diketiminato copper(II) nitrito complex [ClNN]Cu(κ-ON)·THF, thiols mediate reduction of nitrite to NO. In contrast to NO generation upon reaction of thiols at iron nitrite species, at copper this conversion proceeds through nucleophilic attack of thiol RSH on the bound nitrite in [Cu](κ-ON) that le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 40 publications
6
101
0
Order By: Relevance
“…The mechanism for s-bond activation of the HÀH, HÀNa nd HÀPb onds by the NacNacAl I complex, as experimentally reported, [15] was carefullyi nvestigated with DFT.I tw as observed that the solventw as far from as pectator in this chemistry:i t actively and explicitly participated in the s-bond activation process and had as ignificant effect on the efficiency.T he current work therefore reveals that aluminum I chemistry,f or the cases studied, is richer and more complex than had been realized, andi sa ctually an example of metal-solventc ooperativity. Althought here are examples of solvent bindinga saligand in transition-metal complexes, [46,47] to the best of our knowledge, this is the first example of its kind in main-group chemistry, not only of solvent binding as al igand,b ut also of metal-solvent cooperativity.I ndeed, as shown in Figure 13, we had to Figure 9. The free energy profile (DG in kcalmol À1 )for the formationo fh' (hexane-NacNacAl III complex)b yactivationoft he terminalC ÀHb ond.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The mechanism for s-bond activation of the HÀH, HÀNa nd HÀPb onds by the NacNacAl I complex, as experimentally reported, [15] was carefullyi nvestigated with DFT.I tw as observed that the solventw as far from as pectator in this chemistry:i t actively and explicitly participated in the s-bond activation process and had as ignificant effect on the efficiency.T he current work therefore reveals that aluminum I chemistry,f or the cases studied, is richer and more complex than had been realized, andi sa ctually an example of metal-solventc ooperativity. Althought here are examples of solvent bindinga saligand in transition-metal complexes, [46,47] to the best of our knowledge, this is the first example of its kind in main-group chemistry, not only of solvent binding as al igand,b ut also of metal-solvent cooperativity.I ndeed, as shown in Figure 13, we had to Figure 9. The free energy profile (DG in kcalmol À1 )for the formationo fh' (hexane-NacNacAl III complex)b yactivationoft he terminalC ÀHb ond.…”
Section: Resultsmentioning
confidence: 72%
“…The current work therefore reveals that aluminum I chemistry, for the cases studied, is richer and more complex than had been realized, and is actually an example of metal–solvent cooperativity. Although there are examples of solvent binding as a ligand in transition‐metal complexes, to the best of our knowledge, this is the first example of its kind in main‐group chemistry, not only of solvent binding as a ligand, but also of metal–solvent cooperativity. Indeed, as shown in Figure , we had to take the log plot of the relative efficiencies, with and without the explicit assistance of the solvent, to fit the relative efficiency values for different cases of σ‐bond activation by the aluminum I complex into a single graph.…”
Section: Resultsmentioning
confidence: 87%
“…[37] Additionally,t he isoelectronic and isostructural [Br 3 CuNO] À analog performs similar N-, O-, and S-nitrosylation in 93 %, 91 %, 18 %yields,respectively.The low yield of [Br 3 CuNO] À promoted S-nitrosylation is perhaps due to its weak NOC binding affinity. Consistent with the NO-based LUNO,w ef ound that [Cl 3 CuNO] À performs reductive nitrosylation of N-, O-, and S-based nucleophiles, producing N-, O-, S-nitroso compounds in 93 %, 95 %, and 77 %y ield, respectively (Scheme 3).…”
Section: Angewandte Chemiementioning
confidence: 94%
“…The reactivity of [Cl 3 CuNO] À compounds mirrors that of the copper(II) nitrite complex [Cl 2 NN F6 ]Cu II (k 2 -O 2 N), adding further implications for nitrite-derived nitrosative reactivity. [37] Additionally,t he isoelectronic and isostructural [Br 3 CuNO] À analog performs similar N-, O-, and S-nitrosylation in 93 %, 91 %, 18 %yields,respectively.The low yield of [Br 3 CuNO] À promoted S-nitrosylation is perhaps due to its weak NOC binding affinity.…”
Section: Angewandte Chemiementioning
confidence: 94%
“…The S ‐nitrosylation reactivity of [Cl 3 CuNO] − represents the first example of such occurring via a discrete copper nitrosyl complex. The reactivity of [Cl 3 CuNO] − compounds mirrors that of the copper(II) nitrite complex [Cl 2 NN F6 ]Cu II (κ 2 ‐O 2 N), adding further implications for nitrite‐derived nitrosative reactivity . Additionally, the isoelectronic and isostructural [Br 3 CuNO] − analog performs similar N ‐, O ‐, and S ‐nitrosylation in 93 %, 91 %, 18 % yields, respectively.…”
Section: Methodsmentioning
confidence: 99%